It's lonely at the bottom (too): The effects of experienced powerlessness on social closeness and disengagement. Issue 2 (14th October 2019) - Foulk, Trevor A.; De Pater, Irene E.; Schaerer, Michael; du Plessis, Christilene; Lee, Randy; Erez, Amir
Abstract: Although "powerlessness" is a pervasive experience for employees, prior social power research has predominantly focused on consequences of "powerfulness." This has led to contradictory predictions for how experienced powerlessness influences employees' social perceptions and behaviors. To resolve this theoretical tension, we build on Social Distance Theory (Magee & Smith) to develop a theoretical model suggesting that experienced powerlessness reduces social closeness and subsequently causes social disengagement behaviors both at work (reduced helping and increased interaction avoidance) and at home (increased withdrawal). Our model also elucidates the processes that cause powerlessness to reduce social closeness, demonstrating that employees' affiliation motive and their expectation of others' interest in affiliating explain this relationship. We further propose that the effect of powerlessness on social closeness will be stronger for employees high (vs. low) in political skill because these employees are more attuned to workplace power dynamics. We find support for our model in an experience‐sampling field experiment and two experimental scenario studies. Our research clarifies the effects of powerlessness on social closeness and organizationally relevant downstream consequences, qualifies dominant assumptions that the powerless always behave in ways opposite those of the powerful, and demonstrates the importance of political skill as a moderator of power's effects.